2011
DOI: 10.1007/s10778-011-0497-3
|View full text |Cite
|
Sign up to set email alerts
|

Active damping of the resonant vibrations of a flexible cylindrical panel with sensors and actuators

Abstract: The active damping of the resonant vibrations of a flexible cylindrical panel with rectangular planform and clamped edges is considered. The damping is done with distributed piezoelectric sensors and actuators. It is shown that the amplitude of the resonant vibrations can be substantially decreased by choosing the appropriate feedback factors. The combined effect of geometrical nonlinearity and dissipative properties of the material on the effectiveness of damping is analyzed Keywords: piezoelectric sensor, pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The Koltunov Rzhanitsyn singular kernel with three rheological parameters was used for the viscoe lastic model and it was observed that an increase in the concen trated mass leads to a sharp drop in the frequency and amplitude of the panel. The effect of damping on the non stationary vibra tions of a viscoelastic simply supported cylindrical panel with distributed piezoelectric sensors and actuators was investigated by Karnaukhov and Tkachenko [188]. An integral viscoelastic model was used to describe the viscoelastic behavior of the material, and the effect of viscosity and geometric non linearity on the resonant vibrations of the cylindrical panel was discussed.…”
Section: Cylindrical and Doubly Curved Panelsmentioning
confidence: 99%
“…The Koltunov Rzhanitsyn singular kernel with three rheological parameters was used for the viscoe lastic model and it was observed that an increase in the concen trated mass leads to a sharp drop in the frequency and amplitude of the panel. The effect of damping on the non stationary vibra tions of a viscoelastic simply supported cylindrical panel with distributed piezoelectric sensors and actuators was investigated by Karnaukhov and Tkachenko [188]. An integral viscoelastic model was used to describe the viscoelastic behavior of the material, and the effect of viscosity and geometric non linearity on the resonant vibrations of the cylindrical panel was discussed.…”
Section: Cylindrical and Doubly Curved Panelsmentioning
confidence: 99%